Comparative analysis of the organizational culture in finnancial entities from Arequipa - Luna Cáceres, Enrique (2022)
In this research the organizational culture was assessed in four finnancial entities in Arequipa City base on a comparative analysis. There were 100 workers who participate in the sample and the Cameron and Quinn’s Organizational Culture Diagnosing Questionnaire (α= .793) was applied. The results indicate that in the four entities the culture orientated to the Market and Hierarquical type are stronger, but there were evidence about significant differences according to the sex and the enterprise where the workers come, so women tend to percieve a culture type Clan more than male cratic and Clan type organizational culture.